PELATIHAN ADOBE PREMIER DAN IMPLEMENTASINYA PADA PEMBUATAN FILM DURASI PENDEK DI SMKN 1 NEGERI KATON - Hary Sabita; Yuni Puspita Sari; Rionaldi Ali (Institut Informatika dan Bisnis Darmajaya, 2022)
One of the entertainments that is still an attraction in the community is movies. The need for talent in the world of film continues to be needed. SMKN 1 Negeri Katon as one of the vocational schools that has a multimedia major has prepared its students to play a role in the world of movie production. To support this, the school has collaborated with the Darmajaya Institute of Informatics and Business to improve students' competence in the multimedia field, especially moviemaking. Lecturers who are members of this service use Adobe Premiere. This service activities lasted for 2 days and was attended by 70 students from two classes. At the end of the training, the students were given the task of making a short movie. The result achieved is that all students can implement Adobe Premiere and produce movies with short durations. Although not optimal, but in general they can use it for the needs of making a simple movie production